Analisis kesulitan kemampuan komunikasi matematika mahasiswa menggunakan aplikasi google classroom pada matakuliah aljabar - Fitriani, Fitriani; Siregar, Yulia Anita; Novitasari, Wiwik (Journal of Didactic Mathematics, 2021)
Mathematical communication skills are one of the abilities that students must have to make it easier to solve problems contained in mathematics itself and in everyday life. Because if students have mastered mathematical communication skills, it will make it easier for students to take deeper learning. This study aims to analyze the difficulty of students' mathematical communication skills using the Google Classroom Application in the Algebra course. This type of research is descriptive qualitative. The subjects of this study were tree semester students who took Algebra courses in the Mathematics Education study program at Universitas Muhammadiyah Tapanuli Selatan, academic year 2020/2021 as many as 15 people. The instrument used in this study was Test and interview. The results showed that based on the test results obtained: difficulties in the ability to interpret mathematical ideas rationally in writing, difficulties in mathematical problems into mathematical models and difficulties in the ability to express mathematical ideas in the form of descriptions. Meanwhile, based on the results of the interview, namely: (1) technical difficulties, and (2) student adaptation difficulties. To overcome these difficulties, it is necessary which is a combination of Online and Offline learning or also called blended learning.